Turning Waste into Wealth: Exploring Sustainable Plastic Management Pathways in Karisimbi Commune, Goma City, DRC (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the potential and challenges for sustainable plastic waste management in Karisimbi Commune, Goma City, North Kivu Province in DRC. It aimed to identify infrastructural and institutional gaps, assessed community attitudes and practices, explored local recycling initiatives, and proposed improvement strategies. Using a mixed-method approach involving surveys, interviews and observations, the study founded major infrastructural shortcomings, notably poor waste collection systems, limited sorting and recycling facilities, and difficult access in densely populated areas. Findings showed that most respondents agreed there were a lack of designated plastic waste collection points (Mean = 3.33; SD = 1.40), indicating a strong perception of inadequate infrastructure, further exacerbated by weak policy enforcement and limited institutional capacity. Although awareness of plastic waste hazards is high, unsustainable behaviors persist. Nonetheless, local initiatives such as NGOs partnerships, youth-led cleanup campaigns, and informal recycling efforts demonstrated growing community engagement. The study recommended decentralized waste governance, strengthened public-private partnerships and environmental education to enhance sustainable plastic waste management and urban environmental resilience in Karisimbi commune and beyond.